Penentuan Nilai Emisivitas Warna Menggunakan Penerangan Pada Miniatur Ruang Berbentuk Kubus Dan Proses Pembelajaran Fisika Kelas X SMK Negeri 2 Bengkulu Tengah - Cariti Dassa Urra; Afrizal Mayub; M Farid (University of Bengkulu, 2017)
ABSTRACT This study aims to: know the value of emissivity of purple, green, blue, red, light green, light blue, orange, yellow, pink, and improvement of learning outcomes by using PBL model on the concept of heat transfer class X TKR SMKN 2 Bengkulu Tengah, and explain the difference of students' cognitive learning outcomes in high, medium and low group. This study deals with the measurement of color emissivity and its implementation in physics learning on the topic of heat transfer. The population in this study is all students of class X SMK Negeri 2 Bengkulu Tengah academic year 2016/2017. The sample is taken by purposive sampling technique, that is class X.TKR (Light Vehicle Technique) which is taught by Problem Based Learning (PBL) model. This research is a quasi experimental research with One Group pretest-posttest design. The results showed that the purple comet value was 0.91, the green emissivity (going green) was 0.84, the blue emissivity (true blue) was 0.77, the red color emissivity (talk of the town) 0.66, light green color emissivity (apple martini) of 0.61, blue sky emissivity of 0.54, orange torch emission of 0,50, emissivity of light brown (pastry puff) of 0.46, yellow color emission (absolute yellow) of 0.37, and pink emissivity (crystal pink) of 0.24; There is an increase in learning outcomes on the concept of high, medium and low group high caloric transfer with N-gain values of 0.76 (high), 0.64 (medium), and 0.46 (moderate); There was a difference of students' cognitive learning outcomes in the high, medium and low groups shown by Fcount> Ftable (4.40> 3.35) at the 5% significance level.